2022
DOI: 10.3390/jrfm15030122
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Inclusion and Competitiveness on Financial Stability: Why Financial Regulation Matters in Developing Countries?

Abstract: This study aims to assess the effect of financial inclusion and competitiveness on banks’ financial stability, considering the moderating role of financial regulation. To do so, we compare the effects of these variables in Sub-Saharan African (SSA) and Latin American and Caribbean (LAC) countries. Our results suggest that inclusion enhances bank stability in SSA and LAC countries, and financial regulation contributes to increasing financial stability in LAC countries, while we find no statistical significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 63 publications
(140 reference statements)
0
32
0
Order By: Relevance
“…Al-Eitan et al (2022) findings indicated that the number of loan accounts and size of deposits significantly impacted the financial performance of the commercial banks in Jordan negatively. Jungo et al (2022) result indicated that there is no statistically significant effect of financial regulation on financial stability in SSA countries. Maity and Sahu's (2021) result indicated that a significant difference between Assam and aggregate Indian financial inclusion and the status of Assam is somewhat lower as compared to the aggregate financial inclusion status of India.…”
Section: Introductionmentioning
confidence: 90%
“…Al-Eitan et al (2022) findings indicated that the number of loan accounts and size of deposits significantly impacted the financial performance of the commercial banks in Jordan negatively. Jungo et al (2022) result indicated that there is no statistically significant effect of financial regulation on financial stability in SSA countries. Maity and Sahu's (2021) result indicated that a significant difference between Assam and aggregate Indian financial inclusion and the status of Assam is somewhat lower as compared to the aggregate financial inclusion status of India.…”
Section: Introductionmentioning
confidence: 90%
“…Several indicators have been used to assess the extent of financial inclusion, which can be classified into accessibility, availability and usage dimensions. However, the use of an individual indicator may lead to partial information and a misleading conclusion; therefore, we proposed a composite index [19,20,53,54]. On the other hand, there are various financial stability indicators that are linked to financial soundness, stress testing and financial sector development [4,31,48].…”
Section: Methodsmentioning
confidence: 99%
“…The public interest theory of regulation proposed by Kern (2019) suggests that governments could take policy and regulatory interventions to deal with negative externalities generated by market distortions and regulatory arbitrage. Effective financial regulation could improve the production efficiency of enterprises by eliminating systemic risks (Kou et al, 2022), enhancing asset quality and capital levels (Igan & Mirzaei, 2020), limiting unsustainable bank credit expansion (Gupta & Kashiramka, 2020), and preventing financial instability (Anarfo et al, 2020;Jungo et al, 2022). Thus, financial regulation is unquestionably important to maintain a fair playing field inside and between financial systems, ensure the soundness and resilience of banking systems and protect the orderly running of businesses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reasons why the efficiency scores of financing and R&D in SMEs in coastal and non-coastal areas of China increased after adding the intensity of financial regulation are as follows. Firstly, effective financial regulation could maintain financial stability (Rizwan et al, 2018;Jungo et al, 2022). By supervising the activities of financial institutions and enterprises, it is possible to prevent the financial system from being disordered and improve the efficiency of resource allocation (Badertscher et al, 2013;Shroff et al, 2017).…”
Section: The Influence Of Financial Regulation On the Efficiency Of I...mentioning
confidence: 99%
See 1 more Smart Citation